Correlates Of Delayed Immunization: A Cross Sectional Study at A Tertiary Care Centre of Maharashtra, India - Holambe, Vimal M; Thakur, Namrata A (National Journal of Community Medicine, 2013)
Introduction: Immunization programme is one of the most cost-effective public health measures. Even though vaccines are provided at all the government health care centres free of cost, the immunization coverage in India is low. Even amongst these immunized children there appears to be a delay in vaccination of the child. Aim: Present study was conducted to assess the reasons for delay in immunization of infants and determine the factors influencing the timeliness of vaccination. Methodology: A cross sectional study was conducted in Government Medical College, Latur(Maharashtra) during May 2013 to June 2013. The study population consisted of 197 mother-infant pairs attending the Immunization Clinic. Data was collected by direct interview using predesigned and pretested questionnaire. Results: Out of the 197 study subjects, 67(34%) had presented late for immunization. The most common reason for late presentation was that “the family was out of place” on the scheduled day of vaccination. Age of mother at marriage and parity were found to be statistically significantly associated with delayed immunization. Conclusions: Age of mother at marriage and parity are significantly associated with delayed immunization.